THE INFLUENCE OF INFLATION AND THE RUPIAH EXCHANGE RATE ON THE SURVIVAL OF HAJJ COSTS IN SURABAYA(2012 – 2022) - Mahfudloh, Filla Apriliani; Amalina, Sayyida (Economic and Science Faculty of Islamic State University, 2024)
This research aims to explore the phenomenon of Hajj costs which are currently experiencing a significant increase. However, the limited departure quota causes the waiting period for departure to be very long. Less than optimal management of Hajj funds has an impact on increasing Hajj costs. The increase in the cost of Hajj is also influenced by economic and social factors, including the national inflation rate and fluctuations in the rupiah exchange rate against foreign currencies, namely the dollar. The high level of inflation affects the investments made by BPKH which is also a determining factor in the amount of Hajj Organizing Costs (BPIH). Likewise, the exchange rate of the rupiah against the US dollar as a comparative currency which is always fluctuating can cause uncertainty and instability in the economy, so that fluctuations in the value of the US dollar against the rupiah and vice versa will affect the determination of the Cost of Organizing the Hajj Pilgrimage (BPIH). This research was conducted in the city of Surabaya because Surabaya embarkation has the highest Hajj travel costs compared to other cities. This research aims to find the influence of inflation and the rupiah exchange rate on the increase in Hajj costs in Surabaya City during the 2012-2022 period. This research is quantitative research and multiple linear regression analysis techniques using secondary data sourced from BPS, Bank Indonesia, and the Ministry of Religion in the form of annual and monthly data for 2012-2022. The results of the research show that the variables inflation, the rupiah exchange rate simultaneously and significantly have an influence on the increase in the cost of Hajj in Surabaya City during the 2012-2022 period. And partially, the variables inflation and the rupiah exchange rate have a positive and significant effect on the increase in the cost of Hajj in Surabaya City for the 2012-2022 period.